COMPARISON OF ALTERNATIVE METHODS OF RESEARCH THE AREA OF SOIL CONTAMINATION - Камаєва, Інеса Олегівна; Камаєва, Лідія Іванівна; Лев, Олег Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The method for determining the concentration field contamination of soil in areas of complex (unprotuberant)shape is offered and its approbation is conducted. The presented approach is based on the method of weighing measures.